PENGARUH PEMBERIAN KONSELING GIZI TERHADAP PENGETAHUAN DAN SIKAP TENTANG GIZI SEIMBANG PADA LANSIA (Politeknik Kesehatan Kemenkes Bandung, 2021)
Seniors are a group of people aged 60 and above. This group needs special attention, given that its numbers are increasing. The increasing number of elderly will cause complex problems for the elderly, family and society covering physical, biological, mental and socio-economic aspects. Along with these problems, it will affect the intake of eating, which can ultimately affect the nutritional status—objective: To know the effect of counselling on knowledge and attitude about balanced nutrition in the Elderly. The study was conducted in January-March 2018 in the Posbindu Cibeber area of ​​Cimahi City. The study design used a quasi-experimental study with one group pretest-posttest Without Control Group Design. The population of this study is elderly with ages ranging from 60-69 years without complex comorbidities. Samples were taken in Posbindu Karya Budi Asih by purposive sampling with a total sample of 20 people. Types of data used are characteristics, data on eating habits/diet, anthropometry, knowledge data and sample attitudes before and after counselling of balanced nutrition for the Elderly. The result of pre and post-test show that knowledge of balanced nutrition for the elderly was p 0,00 (<0,05). It shows counselling influence to the knowledge of the message of nutrition-balanced for the elderly. Likewise, the results of pretest and post-test showed that balanced nutrition attitude for the elderly is p 0,00 (<0,05). It showed the influence of counselling influence to the attitude of balanced nutrition to the elderly.